Direct hypothalamic and indirect trans-pallidal, trans-thalamic, or trans-septal control of accumbens signaling and their roles in food intake - Urstadt, Kevin R.; Stanley, B. Glenn (Frontiers in Systems Neuroscience, 2015)
Due in part to the increasing incidence of obesity in developed nations, recent research aims to elucidate neural circuits that motivate humans to overeat. Earlier research has described how the nucleus accumbens shell (AcbSh) motivates organisms to feed by activating neuronal populations in the lateral hypothalamus (LH). However, more recent research suggests that the LH may in turn communicate with the AcbSh, both directly and indirectly, to re-tune the motivation to consume foods with homeostatic and food-related sensory signals. Here, we discuss the functional and anatomical evidence for an LH to AcbSh connection and its role in eating behaviors. The LH appears to modulate Acb activity directly, using neurotransmitters such as hypocretin/orexin or melanin concentrating hormone. The LH also indirectly regulates AcbSh activity through certain subcortical "relay" regions, such as the lateral septum, ventral pallidum, and paraventricular thalamus, using a variety of neurotransmitters. This review aims to summarize studies on these topics and outline a model by which LH circuits processing energy balance can modulate AcbSh neural activity to regulate feeding behavior.